Assessing the Writing Skills of Entry-Level Undergraduate Business Students to Enhance their Writing Development during Tertiary Studies - Briguglio, Carmela (Springer, 2007)
Curtin Business School (CBS) in Western Australia has an extremely diverse first year intake into itsbusiness courses, including local and international students from a variety of national, cultural andlingustic backgrounds. Of all the English language skills students require, academic writing is the areawhich poses most challenges for them. A group of staff have therefore collaborated to develop a diagnostic assessment task to be taken by all first year students, with results reported on a six-band scale developed for this purpose. The task was developed in 2003 and repeated In 2004 and 2005, In 2005 a series of special academic writing seminars was developed for those students identified as requiring support. This paper describes the development of the instrument and the scales, the Implementation of trial assessments and refinements; and the sort of support seminars that were implemented to help students to continue to develop academic writing skills.